Gamma Irradiation Doses reduce Cooking time and Improve Nutritional Profile of selected Pigeon pea [Cajanus cajan (L.) Millsp] Genotypes in Nigeria - DAUDU, O.A.Y (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
Pigeon Pea (Cajanus cajan L.) is a self-pollinating perennial legume shrub with over 30,000 accessions deposited world-wide. Despite the nutritional importance of pigeon peas, its detrimental traits such as its long cooking time, has led to low cultivation of the crop and inhibit its consumers’ request. Concerted efforts to improve both the quality and quantity of this crop through mutation breeding informed this research. It was based on this premise that the study was aimed to evaluate gamma irradiation influences on the nutrient quality and cooking duration of selected pigeon pea varieties in Nigeria. Four accessions of pigeon peas (‘NG/SA/11/08/108’, ‘NG/AO/MAY/00/021/01’, ‘TCC-2’ and ‘NG/SA/07/191’) were obtained from National Centre for Genetic Resources and Biotechnology (NACGRAB), Ibadan. They were irradiated at the Oncological Department ABU Teaching Hospital, Shika, Zaria, using Cobalt-60 (60CO) irradiation source. Standard procedures were followed to determine the effects of the irradiation on cookability and nutritional profile of the M1 plants and their respective controls. It was established that all the parameters tested were irradiation dose dependent. In NG/AO/MAY/00/021/01, 100 Gy produced the highest protein (20.40 %) and highest carbohydrate (68.93 %) contents. Anti-nutritional factors such as cyanide were lower (48.83, 46.22, 43.65 and 44.75 mg/kg in NG/AO/MAY/00/021/01, NG/SA/11/08/108, NG/SA/07/191 and TCC-2) at 400 Gy than those of their respective controls (54.83, 56.83, 53. and 53.55 mg/kg). The amount of Magnesium increased with higher doses of gamma irradiation (1.37 g/100 g for 200 Gy NG/AO/MAY/00/021/01; 1.03 g/100g for 400 Gy NG/SA/11/08/108 and 1.13 g/100 g for TCC-2). There were significant reductions in cooking time in 400 Gy treatments for all the genotypes. The differences between the control and the least cooking time in 400 Gy were 11, 16, 22 and 15 minutes for NG/AO/MAY/00/021/01, NG/SA/11/08/108, NG/SA/07/191 and TCC-2, respectively. It was therefore concluded that these variations could be exploited for further improvement of the crop for food security. Keywords: Cooking time, Mutation breeding, Gamma irradiation, Cookability, Dose dependent